Intelligent credit scoring system using knowledge management - Bazzi Mehdi; Chamlal Hasna; El Kharroubi Ahmed; Ouaderhman Tayeb (IAES International Journal of Artificial Intelligence (IJ-AI), 2019)
Promoting entrepreneurship among Moroccan young people has been challenged by a plethora of economic and social problems in the aftermath of the Arab Spring. Several government programs have been set up for young entrepreneurs. Thus, faced with the large number of credit applications solicited by these young entrepreneurs, banks resorted to artificial intelligence techniques. In this respect, this article aims at proposing a decision-making system enabling the bank to automate its credit granting process. It is a tool that allows the bank, in the first instance, to select promising projects through a scoring approach adapted to this segment of entrepreneurs. In the second step, the tool allows the setting of the maximum credit amount to be allocated to the selected project. Finally, based on the knowledge of the bank’s experts, the tool proposes a breakdown of the amount granted by the bank into several products adapted to the needs of the entrepreneur.